2017
DOI: 10.3389/fneur.2017.00615
|View full text |Cite
|
Sign up to set email alerts
|

Structural Covariance of Sensory Networks, the Cerebellum, and Amygdala in Autism Spectrum Disorder

Abstract: Sensory dysfunction is a core symptom of autism spectrum disorder (ASD), and abnormalities with sensory responsivity and processing can be extremely debilitating to ASD patients and their families. However, relatively little is known about the underlying neuroanatomical and neurophysiological factors that lead to sensory abnormalities in ASD. Investigation into these aspects of ASD could lead to significant advancements in our general knowledge about ASD, as well as provide targets for treatment and inform dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
34
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 95 publications
0
34
0
3
Order By: Relevance
“…A consistent observation of these studies includes reduced long-distance cortical FC in individuals with ASD, with effects most pronounced within sensorimotor, default mode, and visual perceptual networks (Assaf et al, 2010; Di Martino et al, 2014; Hahamy et al, 2015). Recent studies showed decreased cerebellar connectivity to somatomotor and visual cortices in ASD relative to controls that was related to more severe ASD symptoms (Khan et al, 2015; Cardon et al, 2017). These findings suggest that intrinsic functional communication between discrete regions of visual–motor brain networks may be selectively impaired in ASD and related to key clinical features of the disorder.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A consistent observation of these studies includes reduced long-distance cortical FC in individuals with ASD, with effects most pronounced within sensorimotor, default mode, and visual perceptual networks (Assaf et al, 2010; Di Martino et al, 2014; Hahamy et al, 2015). Recent studies showed decreased cerebellar connectivity to somatomotor and visual cortices in ASD relative to controls that was related to more severe ASD symptoms (Khan et al, 2015; Cardon et al, 2017). These findings suggest that intrinsic functional communication between discrete regions of visual–motor brain networks may be selectively impaired in ASD and related to key clinical features of the disorder.…”
Section: Introductionmentioning
confidence: 99%
“…FC between brain regions identified as significant in our ALFF–force variability analysis was then compared between groups and examined in relation to visuomotor behavior. Given prior findings that more severe motor abnormalities (Haswell et al, 2009; Estes et al, 2015; Landa et al, 2016) and FC alterations (Khan et al, 2015; Cardon et al, 2017) of visuomotor networks are associated with more severe ASD symptoms, we also examined the relationship between visuomotor network ALFF and FC with clinical ratings of social–communication abnormalities and restricted and repetitive behaviors in individuals with ASD.…”
Section: Introductionmentioning
confidence: 99%
“…Several diffusion tensor imaging (DTI) studies of ASD have shown alterations of WM microstructure in the pathways linking the cerebellum to the brainstem and cerebral hemispheres (Brito et al, 2009 ; Shukla et al, 2010 ; Groen et al, 2011 ; Jeong et al, 2012 ). A 2017 structural MRI study of individuals with ASD showed differences in morphological connectivity among neuroanatomical areas implicated in sensory processing, including sensory regions of the cerebral cortex, the amygdala, and the cerebellum, with altered connectivity between the cerebellum and cortical areas (Cardon et al, 2017 ). Moreover, the cerebellum plays a role in multisensory processing, as its connectivity to the cerebral cortex is important for sensory integration across different modalities such as hearing, sight, touch and even smell (Cardon et al, 2017 ; Zhao et al, 2018 ; Sathyanesan et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…A 2017 structural MRI study of individuals with ASD showed differences in morphological connectivity among neuroanatomical areas implicated in sensory processing, including sensory regions of the cerebral cortex, the amygdala, and the cerebellum, with altered connectivity between the cerebellum and cortical areas (Cardon et al, 2017 ). Moreover, the cerebellum plays a role in multisensory processing, as its connectivity to the cerebral cortex is important for sensory integration across different modalities such as hearing, sight, touch and even smell (Cardon et al, 2017 ; Zhao et al, 2018 ; Sathyanesan et al, 2019 ). While investigation of the structural and functional aspects of sensory processing has begun in children with isolated SPD and those with sensory over-responsivity and autism (Bar-Shalita et al, 2009 ; Marco et al, 2011 ; Brandes-Aitken et al, 2018 ; Molholm et al, 2020 ), there has so far been no exploration of the role of the cerebellum in children with isolated SPD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation